Auditoría de gestión al área de recursos humanos en la Unidad Educativa Calasanz de la ciudad de Loja, periodo 2022 - Delgado Gualpa, Adriana Katherine (2024)
The present work entitled “Management Audit of the Human Resources Area in the Calasanz Educational Unit of the city of Loja, period 2022”., is oriented towards the application of the management audit, to establish the degree of control maintained by the institution. within the human resources area, to what corresponds to its administrative and operational activities, through the evaluation of internal control, in order to determine compliance with institutional objectives, through which the application of the internal control questionnaire was carried out and management indicators that allow measuring efficiency and effectiveness, which verifies compliance with Laws, Rules and Regulations in the development of its activities, and through this issue a report that includes comments, conclusions and recommendations related to the findings identified in the process of audit, demonstrating the situation in which the educational institution is located. To meet these objectives, the Audit phases were developed, starting with planning, within which the prior visit to the institution subject to the audit was carried out, where information related to the Human Resources Area was collected, through of the interview, which allowed the audit program to be carried out and thereby determine the procedures to be used, then the management indicators were applied to determine the effectiveness, efficiency and thereby establish the level of performance and behavior of the staff, with respect to to its activities, achieving an analysis of the real situation in which the institution finds itself, with this it was possible to verify that there are no significant findings, and that the institution is in a very good rating range in terms of the development of activities. As a result of the audit, the Final Report is prepared, which is submitted to the consideration of the rector and other authorities of the institution, which includes comments, conclusions and recommendations, among the main ones being that the entity does not There is an annual operational plan in accordance with the Internal Control Standards of the State Comptroller General's Office, as well as an updated procedures manual. Not all staff know the Institutional philosophy that guides their activity. There is a lack of control over attendance and permanence. In their jobs, in the employment stability indicator, it was verified that all administrative staff are hired, in the attendance indicator it was determined that they have attended mostly on the scheduled days. These will serve for its managers and administrators to take actions or measures that lead to strengthening the internal control system and institutional management and activities developed by the Human Talent Area.